Improving antibody-based therapies by chemical engineering of antibodies with multimeric cell-penetrating peptides for elevated intracellular delivery - Sauter, Max; Strieker, Matthias; Kleist, Christian; Wischnjow, Artjom; Daniel, Volker; Altmann, Annette; Haberkorn, Uwe; Mier, Walter (Journal of controlled release, 2020)
Monoclonal antibodies (mAbs) are increasingly exploited as vehicles for the targeted delivery of cytotoxic drugs. In antibody-drug conjugates (ADCs) antibodies specifically deliver cytotoxic compounds to cancer cells. Here, we present a technology for elevating the intracellular delivery of antibodies by the conjugation of tetrameric cell-penetrating peptides (tCPPs). The solid phase synthesis of tCPPs and their application in a chemical modification strategy for mAbs provides constructs that attain up to fourfold elevated internalization rates while retaining the mAbs target specificity. The antigen independent internalization is accompanied by beneficial pharmacokinetics limiting off-target accumulation. Applicability was proven for matuzumab, trastuzumab and the ADC Kadcyla®. Cytotoxicity studies of tCPP-conjugates of Kadcyla® resulted in a sixfold increased cytotoxicity proving the potential of chemical modification strategies to extend the applicability of biologicals. This constitutes a significant step towards next-generation antibody-based therapeutics.
Gesehen am 22.03.2021